Uninterrupted Expression of CmSIT1 in a Sclerotial Parasite Coniothyrium minitans Leads to Reduced Growth and Enhanced Antifungal Ability - Sun, Xiping; Zhao, Ying; Jia, Jichun; Xie, Jiatao; Cheng, Jiasen; Liu, Huiquan; Jiang, Daohong; Fu, Yanping (Frontiers in Microbiology, 2017)
Coniothyrium minitans is an important mycoparasite of Sclerotinia sclerotiorum. In addition, it also produces small amounts of antifungal substances. ZS-1TN1812, an abnormal mutant, was originally screened from a T-DNA insertional library. This mutant showed abnormal growth phenotype and could significantly inhibit the growth of S. sclerotiorum when dual-cultured on a PDA plate. When spraying the filtrate of ZS-1TN1812 on the leaves of rapeseed, S. sclerotiorum infection was significantly inhibited, suggesting that the antifungal substances produced by this mutant were effective on rapeseed leaves. The thermo-tolerant antifungal substances could specifically suppress the growth of S. sclerotiorum, but could not significantly suppress the growth of another fungus, Colletotrichum higginsianum. However, C. higginsianum was more sensitive to proteinous antibiotics than S. sclerotiorum. The T-DNA insertion in ZS-1TN1812 activated the expression of CmSIT1, a gene involved in siderophore-mediated iron transport. It was also determined that mutant ZS-1TN1812 produced hypha with high iron levels. In the wild-type strain, ZS-1, CmSIT1 was expressed only when in contact with S. sclerotiorum, and consistent overexpression of CmSIT1 showed similar phenotypes in ZS-1TN1812. Therefore, activated expression of CmSIT1 leads to the enhanced antifungal ability, and CmSIT1 is a potential gene for improving the control of C. minitans.